2008
DOI: 10.1158/0008-5472.can-08-0053
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Uncoupling Protein-2 Promotes Chemoresistance in Cancer Cells

Abstract: Cancer cells acquire drug resistance as a result of selection pressure dictated by unfavorable microenvironments. This survival process is facilitated through efficient control of oxidative stress originating from mitochondria that typically initiates programmed cell death. We show this critical adaptive response in cancer cells to be linked to uncoupling protein-2 (UCP2), a mitochondrial suppressor of reactive oxygen species (ROS). UCP2 is present in drug-resistant lines of various cancer cells and in human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
165
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(178 citation statements)
references
References 30 publications
10
165
1
2
Order By: Relevance
“…48). In leukemia and colon cancer cells, UCP2 overexpression had been reported to have a protumoral effect (49,50). In contrary, in the other tumors derived from cells with very low basal UCP2 expression, including melanoma, UCP2 mRNA expression is decreased (Supplementary Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…48). In leukemia and colon cancer cells, UCP2 overexpression had been reported to have a protumoral effect (49,50). In contrary, in the other tumors derived from cells with very low basal UCP2 expression, including melanoma, UCP2 mRNA expression is decreased (Supplementary Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Further to this, recent reports demonstrated that different cellular component of the BMME can transfer mitochondria to epithelial cells or solid cancer cell lines through heterocellular contacts. [10][11][12] Although recipient cells displayed an improved metabolism, there is no clear evidence that functional mitochondria are actually transferred.…”
Section: Introductionmentioning
confidence: 99%
“…UCP2 has a broad distribution and is implicated in a variety of processes, including regulation of reactive oxygen species production (Arsenijevic et al, 2000), food intake (Andrews et al, 2008), insulin secretion (Zhang et al, 2001) and immunity (Arsenijevic et al, 2000) as well as pathologies including atherosclerosis (Blanc et al, 2003), cancer (Derdak et al, 2008), diabetes (Zhang et al, 2001) and neuronal injury (Sullivan et al, 2003). UCP2 levels vary dynamically in response to nutrients and this is achieved by varied expression rates against a background of a very short UCP2 protein half-life of ~1 hour (Rousset et al, 2007;Giardina et al, 2008;Azzu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%